Exploitation of olive mill wastewater in sorghum irrigation - Rachid Mahmoud; Fatimzahra Ainlhout; Mohamed Ben Abbou; Mustapha Taleb; Mounia El haji; Zakia Rais (International Journal of Recycling of Organic Waste in Agriculture)
Purpose In Morocco, the olive industry has made remarkable progress thanks to the "Green Morocco Plan" adopted by the Ministry of Agriculture. In 2018, the total production was around 2,000,000 tons of olives, with a growth of 11.93% compared to the previous years. However, each year this activity generates millions of tons of liquid and solid pollutants "olive mill wastewater (OMW)" and "pomace", discharged directly into water streams without prior treatment, which creates serious ecological problems.Method This study focuses on the use of raw and diluted OMW for the fertilization of sorghum. The OMW were characterized, diluted (½ and ¼), and applied at a rate of 5 L /week /m2. Sorghum growth was monitored by studying physiological performance (transpiration, stomatal conductance, the intensity of photosynthesis, and the performance of photosystem II).Results The raw OMW is acidic, salty, highly loaded with organic (COD / BOD5 = 7.1> 3), and inorganic matter and polyphenol content of 9 g/L. All the parameters for monitoring the growth of sorghum are lower for plants irrigated by raw OMW, which are symptoms of water stress. Using the T-test, the plants irrigated by half-diluted OMW have yielded the same results as those of the control.Conclusion Despite the fact that the half dilution of OMW has proved promising results, we suggest that it should be pretreated before its use in sorghum irrigation to reduce its organic loads and acidity.